Chronic asthma in adults. Issue 1 (January 2020) - Wiffen, Laura; Gates, Jessica; Brown, Thomas; Rupani, Hitasha; Longstaff, Jayne; Chauhan, AJ
There are around 5.4 million people in the UK with asthma. Poorly controlled asthma places a particular burden on the NHS, and diminishes patients' quality of life. More significantly, there are an estimated 1400 deaths from asthma each year in the UK, many of which are preventable. This is unacceptably high for a treatable condition. General practice carries much of the responsibility for diagnosis and management of asthma, and there is potential to improve the mortality and morbidity rates from asthma by improving knowledge transfer between GPs and their patients and the use of guidelines on compliance with agreed treatment paths. There are three separate sets of guidelines for the diagnosis and treatment of asthma: The British Thoracic Society and Scottish Intercollegiate Guidelines Network guidelines, The National Institute for Health and Care Excellence guidelines, and Global Initiative for Asthma guidelines. These will be reviewed throughout this article.